The Emergence of Group Potency and Its Implications for Team Effectiveness - Woodley, Hayden J. R.; McLarnon, Matthew J. W.; O’Neill, Thomas A. (Frontiers in Psychology, 2019)
Much of the previous research on the emergence of team-level constructs has overlooked their inherently dynamic nature by relying on static, cross-sectional approaches. Although theoretical arguments regarding emergent states have underscored the importance of considering time, minimal work has examined the dynamics of emergent states. In the present research, we address this limitation by investigating the dynamic nature of group potency, a crucial emergent state, over time. Theory around the “better-than-average” effect (i.e., an individual’s tendency to think he/she is better than the average person) suggests that individuals may have elevated expectations of their group’s early potency, but may decrease over time as team members interact gain a more realistic perspective of their group’s potential. In addition, as members gain experience with each other, they will develop a shared understanding of their team’s attributes. The current study used latent growth and consensus emergence modeling to examine how potency changes over time, and its relation with team effectiveness. Further, in accordance with the input-process-output framework, we investigated how group potency mediated the relations between team-level compositions of conscientiousness and extraversion and team effectiveness. We collected data at three time points throughout an engineering design course from 337 first-year engineering students that comprised 77 project teams. Results indicated that group potency decreased over time in a linear trend, and that group consensus increased over time. We also found that teams’ initial potency was a significant predictor of team effectiveness, but that change in potency was not related to team effectiveness. Finally, we found that the indirect effect linking conscientiousness to effectiveness, through initial potency, was supported. Overall, the current study offers a unique understanding of the emergence of group potency, and facilitate a number theoretical and practical implications, which are discussed.